Comparison of methods for the isolation of cell-free DNA from cell culture supernatant - Abel Jacobus Bronkhorst; Vida Ungerer; Stefan Holdenrieder (Tumor Biology)
In vitro characterization of cell-free DNA using two-dimensional cell culture models is emerging as an important step toward an improved understanding of the physical and biological characteristics of cell-free DNA in human biology. However, precise measurement of the cell-free DNA in cell culture medium is highly dependent on the efficacy of the method used for DNA purification, and is often a juncture of experimental confusion. Therefore, in this study, we compared six commercially available cell-free DNA isolation kits for the recovery of cell-free DNA from the cell culture supernatant of a human bone cancer cell line (143B), including two magnetic bead-based manual kits, one automated magnetic bead-based extraction method, and three manual spin-column kits. Based on cell-free DNA quantitation and sizing, using the Qubit dsDNA HS assay and Bioanalyzer HS DNA assay, respectively, the different methods showed significant variability concerning recovery, reproducibility, and size discrimination. These findings highlight the importance of selecting a cell-free DNA extraction method that is appropriate for the aims of a study. For example, mutational analysis of cell-free DNA may be enhanced by a method that favors a high yield or is biased toward the isolation of short cell-free DNA fragments. In contrast, quantitative analysis of cell-free DNA in a comparative setting (e.g. measuring the fluctuation of cell-free DNA levels over time) may require the selection of a cell-free DNA isolation method that forgoes a high recovery for high reproducibility and minimal size bias.